Makna Semiotik Kisah Mimpi Raja dalam Surat Yusuf ayat 43 – 49 : (Analisis Semiotik Charles Sander Peirce) - MA Sofwan Hadi (AN NUR: Jurnal Studi Islam, 2022)
The purpose of this study was to find out the interpretation of the story of the King's dream in Yusuf verses 43 - 49 with Charles Sander Pierce's semiotic analysis. This study used a literary reception research method, namely reader acceptance. The problem that would be examined about the Qashas al-Qur'an/story, was the preaching of the Qur'an about matters of the past people, previous prophecies (prophecy) and events that had occurred. Data collection techniques used literature study. The results showed that the study of the king's dream interpretation in Yusuf verses 43-49 with Charles Sander Pierce's semiotic analysis was as follows. Sign was a king dreamed about seven fat cows being eaten by seven skinny cows and also seven green and dry stalks. The object was that Prophet Yusuf gave the interpretation of the king's dream and the sign user (interpreter) was the reader's interpretation of the dream interpretation by presenting images for easy understanding. About the sentence "Wa Sab'a Sunbulatin Khudrin." It mean seven green grains (wheat), seven green stalks, mayang, stalks (rice), that the word Sunbulatin was in the form of a general sentence, and not ma'rifat. While the sentence khudrin was the nature/na'at of Sunbulatin. So Sunbulatin Khudrin was the green stalk means staple food.